(untitled) (Revista horizonte, 2013)
This article analyzes the accuracy of the ThresholdÂ® IMT in the determination of different levels of resistance: R1=7, R2=15, R3=21, R4=27, R5=35 and R6=41 cm H2O in young obese women, taking maximum inspiratory pressure (MIP) as a reference. METHODS: For this purpose, 21 obese grade I women, with BMI of 34.56 Â± 5.82 kg/m2 and mean age of 44.4 Â± 13.4 years were subjected to MIP measurement through the manometer with subsequent measurement of resistance levels generated by the ThresholdÂ® IMT of R1=7, R2=15, R3=21, R4=27, R5=35 and R6=41 cm H2O. For the normality test, the Shapiro-Wilk test was applied, and for the analysis between the percentages of MIP obtained and the different resistances generated by ThresholdÂ® IMT test, the ANOVA test and repeated measures with the Bonferroni post-hoc significance level of p<0.05 was used. For the determination of the level of association between the resistance values generated by the ThresholdÂ® IMT and the values measured by the manometer the Pearson correlation coefficient was applied. Results and conclusions: The average values obtained for maximal inspiratory pressure (MIP) are below an expected normal pattern -81.56 H2O, confirming that the sample has a deficit for MIP. Comparison of the mean values of the resistances generated by the ThresholdÂ® IMT showed significant differences in Wilks’Î›, F(5;162,087)=16.000, p=0.001 between all resistances observed for a power of 99%. However, the coefficient of variance (CV) observed for the 7 cm H2O resistance was the highest with 23.23%; for15 cm H2O the value was the lowest with 7.09% and there was less variation in the 21 and 27 cm H2O resistance, where the coefficients (CV) were 10.26% and 12.17% respectively. In R5 and R6 the flow generated was below the resistance generated by the device, especially for R6, where a difference of -2.42 cm H2O, on average, is observed between the generated and measured resistance. This result shows a reversal of the behavior of the resistance generated by the device, once the ThresholdÂ® IMT overestimates the loads for the respective resistances. The CV for R5 was 17.02% and 19.75% for R6. While the CV values are below 25% according to the homogeneity data. This demonstrates the low accuracy of the ThresholdÂ® IMT.